TRMT112, a master activator of several methyltransferases modifying factors involved in RNA maturation and translation - Wang, Can; Tay, Laurianne L. E.; Hu, Wanwan; Corre, Morgane; Graille, Marc (Frontiers in RNA Research, 2025)
Most RNAs and many protein factors involved in mRNA maturation and translation are decorated by numerous and diverse chemical modifications, which contribute to the efficiency, fidelity and regulation of these complex and essential cellular processes. Among those modifications, methylation catalyzed mainly by S-adenosyl-L-methionine (SAM) dependent methyltransferases (MTases) is the most common one. TRMT112 is a small protein acting as an allosteric regulator of several MTases. Initial studies focusing on TRMT112 and its associated MTases were performed in Saccharomyces cerevisiae whereas only few were expanded to human cells, leading to the identification and characterization of four TRMT112 partners in yeast (Trm11, Bud23, Mtq2 and Trm9) and five in human cells (TRMT11, BUD23, MTQ2/HemK2 and two Trm9 orthologues ALKBH8 and TRMT9B). Recent studies have identified several novel MTase partners of human TRMT112, namely METTL5, THUMPD2 and THUMPD3. Interestingly, all these TRMT112-MTase complexes modify factors (RNAs and proteins) involved in mRNA maturation and translation processes and growing evidence supports the importance of these MTases in cancer and correct brain development. In this review, we summarize the current knowledge on TRMT112 protein and its various MTase partners in eukaryotes and archaea.